Gamma-radiation induced synthesis of freestanding nickel nanoparticles. Issue 1 (15th December 2020) - Yang, Yi; Johansson, M.; Wiorek, A.; Tarakina, N. V.; Sayed, F.; Mathieu, R.; Jonsson, M.; Soroka, I. L.
Abstract : Freestanding magnetic Ni nanoparticles are obtained by γ-radiation induced synthesis out of aqueous precursor solutions. Abstract : A versatile method to produce metallic nickel nanoparticles is demonstrated. Metallic Ni nanoparticles have been synthesized from aqueous solution of NiCl2 using γ-radiation induced reduction. To prevent Ni re-oxidation, post-irradiation treatment was elaborated. Structural and compositional analyses were executed using X-ray diffraction, transmission electron microscopy and X-ray photoelectron spectroscopy. These studies reveal that the synthesized material consists of fcc Ni particles having size of 3.47 ± 0.71 nm. The nanoparticles have a tendency to agglomerate to the larger clusters. The latter are partially oxidized to form thin amorphous/poor-crystalline Ni(OH)2 /NiO layers at the surface. Magnetization measurements demonstrate that the nanomaterial exhibit ferromagnetic-like behaviour with magnetization 30% lower than that in bulk Ni. The large active surface area (ECSA, 39.2 m 2 g −1 ) and good electrochemical reversibility, confirmed by the electrochemical studies, make the synthesized material a potential candidate as an active component for energy storage devices.